2020
DOI: 10.1002/mcf2.10129
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relative Selectivity of Multiple Sampling Gears for Managed Reef Fishes in the Eastern Gulf of Mexico

Abstract: Fishery-independent data are important for the effective management of reef fishes in the eastern Gulf of Mexico. Proper characterization of selectivity, or the effectiveness of each type of sampling gear in capturing a species or a size-class, is essential to ensure that assessment models treat various sources of data appropriately. In this study, we analyzed fishery-independent data that was collected using stereo-baited remote underwater video (S-BRUV) arrays, chevron traps (TRAP), and two types of hooked g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…2012; Christiansen et al. 2020). We found that modal size of caught fish increased with hook size as was found in other hooked‐gear reef fish studies (Ralston 1990; Otway and Craig 1993; Erzini et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2012; Christiansen et al. 2020). We found that modal size of caught fish increased with hook size as was found in other hooked‐gear reef fish studies (Ralston 1990; Otway and Craig 1993; Erzini et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sample collection.-All sampling was conducted using the repetitive timed-drop (RTD) method, a standardized, active hook-and-line fishing technique developed in collaboration with industry partners (Guenther et al 2013(Guenther et al , 2014Stallings et al 2014;Christiansen et al 2020). Each angler used a rod-and-reel rig consisting of an electric reel drive (12 V DC, Elec-tra-mate model 620D or 940XP), a fishing reel (Diawa Sealine 600H 6/0 or Penn Senator 115 L 9/0) containing Ande 45.4-kg-test monofilament, and a heavyduty fiberglass fishing pole (2.1-2.4 m long).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…La longitud de captura está directamente relacionada a la que alcanza el pez, la zona y profundidad de la pesca y el arte utilizado, que define una selectividad (Christiansen et al 2020). De las 13 especies a las cuales se le analizó la estructura de tallas, solo para siete se encontró información publicada sobre media reproductiva (L 50 ).…”
Section: Discussionunclassified
“…Tagging onboard following capture is known to alter movement behaviour during a prolonged recovery period for lamnid sharks (Hoolihan et al 2011;Bowlby et al 2021) and carcharhinid species (Vaudo et al 2014). Also, our non-capture tagging methodology was unaffected by gear selectivity, unlike capture-based sampling that is known to be size-selective (Maunder et al 2006;Rotherham et al 2007;Christiansen et al 2020).…”
Section: Tagging Methodologymentioning
confidence: 99%